ANALISIS PENGELOMPOKAN DATA BERDASARKAN LAPORAN RL 4A PASIEN RAWAT INAP DI RSUD M. NATSIR SOLOK PERIODE 01 MARET – 31 MARET 2018 - Syamsul Kamal; Nindi Lukita; Yastori Yastori (Iris Journal of Health Information Management, 2021)
Hospital reporting is an organizational tool that aims to be able to produce information quickly, precisely and accurately to hospital management or those who need information. In the process of making the RL 4a report at the Mohammad Natsir Solok Regional Hospital, there were still obstacles. One of the obstacles in processing RL 4a reporting is that inpatient medical record files are not completely filled in and are still being worked on manually. Data collection was carried out at RSUD Mohammad Natsir Solok by recording data on inpatients who returned home from March 1 to March 31, 2018 with a total of 259 patients. The data was processed using a computer using the Microsoft Excel application program. The grouping of reports is based on RL 4a, where after processing the data, it is found that the most age group is the age group 45 to 64 years 54 women and 32 men, followed by the age group 24 to 44 years, where 38 women and 25 men -Male. For the sexes of patients the most were female as many as 158 and male 101 people, then for the disposition 249 were alive and 10 patients died.